2020
DOI: 10.1093/pasj/psaa108
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new extreme changing-state quasar with 4 mag variation, SDSS J125809.31+351943.0

Abstract: We report the discovery of a quasar, SDSS J125809.31+351943.0 (J1258), which brightened in optical wavelengths for 4 mag from 1983 to 2015: one of the largest quasar brightening events so far. The history of optical photometry data of this quasar from the Catalina Real-time Transient Survey and All Sky Automated Survey for Super Novae (ASAS-SN), mid-infrared photometry data from the WISE satellite, and the broad emission line (BEL) flux obtained by spectroscopy of the Sloan Digital Sky Survey shows significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Yang et al (2018) found the MIR Wide-field Infrared Survey Explorer colors of CLQs are redder when brighter, indicating a strong hot dust contribution rather than reddening. In several cases, the IR tracks the optical variability (e.g., Nagoshi et al 2021), again suggesting that obscuration is not the cause of dimming in CLQs.…”
Section: Introductionmentioning
confidence: 85%
“…Yang et al (2018) found the MIR Wide-field Infrared Survey Explorer colors of CLQs are redder when brighter, indicating a strong hot dust contribution rather than reddening. In several cases, the IR tracks the optical variability (e.g., Nagoshi et al 2021), again suggesting that obscuration is not the cause of dimming in CLQs.…”
Section: Introductionmentioning
confidence: 85%
“…"Changing-look" active galactic nuclei (CL-AGNs), which are AGNs with a temporary appearance or disappearance of their broad emission lines, show a spectral transition between Type 1, intermediate type, and Type 2 within a timescale of years to decades (Ricci & Trakhtenbrot 2022;Komossa & Grupe 2023). 5 The CL phenomenon is rare; thus far, with multiepoch photometry and optical spectroscopy, only ∼150 CL-AGNs have been identified (e.g., MacLeod et al 2010MacLeod et al , 2016MacLeod et al , 2019Shapovalova et al 2010;Shappee et al 2014;LaMassa et al 2015;McElroy et al 2016;Parker et al 2016;Ruan et al 2016Ruan et al , 2019Runnoe et al 2016;Gezari et al 2017;Sheng et al 2017Sheng et al , 2020Kollatschny et al 2018Kollatschny et al , 2020Mathur et al 2018;Stern et al 2018;Wang et al 2018Wang et al , 2019Wang et al , 2020aWang et al , 2022Yang et al 2018;Frederick et al 2019;Guo et al 2019;Marin et al 2019;Parker et al 2019;Trakhtenbrot et al 2019;Yan et al 2019;Ai et al 2020;Graham et al 2020;Nagoshi et al 2021;Green et al 2022;Hon et al 2020Hon et al , 2022...…”
Section: Introductionmentioning
confidence: 99%
“…Other potential types of variable objects can be found in Byrne & Fraser (2022). Moreover, extragalactic transients that can be associated to rare blazars or accretion outbursts in active galactic nuclei (Lawrence et al 2016) or highly variable quasars or microlensing events (Nagoshi et al 2021) can also contribute.…”
Section: Discussionmentioning
confidence: 99%